Cu2−xSx Capped AuCu Nanostars for Efficient Plasmonic Photothermal Tumor Treatment in the Second Near‐Infrared Window. Issue 8 (16th December 2021) - Yu, Qian; Peng, Tingyu; Zhang, Jinfeng; Liu, Xiaoxuan; Pan, Ye; Ge, Dengfeng; Zhao, Long; Rosei, Federico; Zhang, Jianming
Abstract: Plasmonic nanohybrids are promising photo energy conversion materials in photoelectronics and biomedicine, due to their unique surface plasmon resonance (SPR). Au and Cu2− x S x nanostructures with strong SPR in the near‐infrared (NIR) spectral region are classic plasmonic systems used to convert NIR photons into heat for photothermal therapy (PTT). The rational design of the Au/Cu2− x S x nanohybrids is expected to induce better photothermal conversion; however, the construction of such hybrids via wet‐chemistry methods with a well‐controlled interfacial structure is still challenging. Here, the synthesis of an AuCu Star/Cu2 −x S x nanohybrid is reported, where the Cu2− x S x components are selectively grown on the AuCu nanostar tips to form "caps". The spatial formation of the Cu2− x S x caps on star tips is mainly governed by surfactant concentration, tip curvature, and experimental manipulation. The nanohybrids show low cytotoxicity and superior photothermal conversion efficiency, enabling robust PTT to kill cancer cells in the second NIR window. Numerical simulation reveals that the coupling of Cu2− x S x on nanostar tips generates strong interfacial electric field, improving photothermal conversion. Moreover, the spatial separation structure favors the continuous flow of hot charge carriers to produce active radicals, further promoting the tumor treatment effect. Abstract : The construction of a structure of AuCu Star/Cu2− x S x nanohybrid is presented, where the Cu2− x S x component is grown selectively on the branch ends of the AuCu nanostars to form "caps". The nanohybrids show low cytotoxicity and excellent photothermal conversion efficiency, leading to superior photothermal performance to kill cancer cells in the second near‐infrared window.